Market demand for and producer profits of certified safe cabbage: evidence from test sales in traditional food markets in Northern Ghana - Lowenstein, W.; Wetzel, C.; Mustapha, I.; Drechsel, Pay; Abubakari, A.-H. (Elsevier, 2024)
Vendors in traditional urban food markets in West Africa offer locally produced vegetables. These may be unsafe, carrying pathogens and posing potential risks to consumers’ health; or safe, being free from pathogens. Safe produce is rarely differentiated from unsafe produce through certification or price differentiation. Consequently, there is no market data on consumers’ actual payments for certified safe vegetables. Therefore, we aimed to find out whether there is a demand for certified safe vegetables and whether such safety certification is profitable for small-scale farmers. Previous studies have used experiments to elicit price premia consumers’ state to be willing to pay. In contrast, we offered pathogen-free cabbage certified as safe on traditional food markets in Tamale, Ghana, and observed what consumers actually paid. We noted consumer’s actual purchases, who – at the same market stalls – chose between ordinary cabbage of unknown safety status and certified safe cabbage, which carried a price premium to be paid in addition to the price of ordinary cabbage. Our results show that 176 consumers purchased certified safe cabbage and 123 bought ordinary cabbage during the test sales. Consumers’ probability to buy certified safe cabbage is explained by the size of the price premium charged, households’ characteristics and perceptions of local production modes. Estimating customers’ demand function for certified safe cabbage revealed that a pioneer farmer should charge a monopolistic price premium of GHS 1.48 (+46 % on top of the average price for ordinary cabbage valid during the test sales) to maximise the profits from introducing certified safe cabbage into the market. We find that the most promising certification option is for groups of geographically concentrated farmers to jointly apply for safe vegetable certification.